2007
DOI: 10.1111/j.1600-6143.2007.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Albumin Excretion and the Risk of Graft Loss and Death in Proteinuric and Non-proteinuric Renal Transplant Recipients

Abstract: Background: Microalbuminuria and macroalbuminuria constitute risk factors for ESRD and death in nontransplanted populations. Whether microalbuminuria (especially in non-proteinuric patients) and macroalbuminuria constitute risk factors for graft loss and death is presently unknown in renal transplantation. Conclusions: Microalbuminuria and macroalbuminuria are powerful independent predictors of ESRD and death. Microalbuminuria is a risk factor for graft loss even in non-proteinuric patients. UAE provides addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 38 publications
3
63
2
2
Order By: Relevance
“…As previously published (11), 616 patients were followed at our institution between 1998 and 2005: both total proteinuria and UAE were measured. Most patients received our institution's immunosuppressive regimen: induction therapy with antithymocyte globulin (Thymoglobulin ® , Sangstat, Lyon, France) or interleukin-2-receptor antagonists (Simulect ® , Novartis, Rueil-Malmaison France).…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously published (11), 616 patients were followed at our institution between 1998 and 2005: both total proteinuria and UAE were measured. Most patients received our institution's immunosuppressive regimen: induction therapy with antithymocyte globulin (Thymoglobulin ® , Sangstat, Lyon, France) or interleukin-2-receptor antagonists (Simulect ® , Novartis, Rueil-Malmaison France).…”
Section: Study Populationmentioning
confidence: 99%
“…Interestingly, it was recently demonstrated that UAE was an independent powerful risk factor for graft loss and death in renal transplant recipients (11). However, it is presently unknown whether NAP has any predictive value on graft loss or death, and therefore whether UAE and NAP provide different information on patient or renal outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, hypertension was associated with significantly worse outcomes in patients with proteinuria [150] . In addition, microalbuminuria has also been found to be a powerful risk factor for increased mortality from CVD [151] . Investigation into the management of proteinuria has found that ACEinhibitors and ARBs are effective in reducing levels of proteinuria, although their overall effect on allograft function and survival are less clear [152,153] .…”
Section: Proteinuriamentioning
confidence: 99%
“…Previous studies in CKD populations have suggested that a decrease in microalbuminuria may lead to the suppression of renal function impairment (12,13) and cardiovascular disease (14-16) progression. In renal transplant recipients, microalbuminuria is a risk factor for graft loss and all-cause mortality (17). The effectiveness of RAS inhibitors for decreasing proteinuria following renal transplantation has been evaluated in various studies (16,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%